Feasibility of the BetterSweet Cake Business at Hollywood Junction: Opportunities and Challenges - Nurul Kholifah; Azzah Muaribah Nabhan; Hikmal Akbar; Cindy Reyna Nurhasanah; Tri Damayanti (Lentera Ilmu Nusantara, 2025)
The BetterSweet Cake business feasibility study analyzes the potential for developing a premium patisserie business in the Cikarang culinary industrial area, using qualitative descriptive methods to evaluate marketing, operational, human resource, and financial aspects. In the marketing aspect, product distribution is designed through offline and online channels. Operationally, the business plans to produce 75 cakes daily with premium quality standards. The human resource approach is competency-based recruitment, continuous development programs, and a motivating compensation system. Financial analysis Working capital strategies and revenue estimates are designed to support sustainable business growth. The method in this study uses a mixed descriptive method of qualitative and quantitative, the results show that BetterSweet Cake has competitive potential in the local patisserie industry, with the latest product innovations.